IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI TERSTRUKTUR UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA MATERI SISTEM PEREDARAN DARAH - Hanifah Nur Rahmadhani; Dyah Astriani (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the implementation of learning, student responses, and improvement of basic science process skills after the implementation of the structured inquiry learning model in the concept human circulatory system. This study was a pre-experimental design with one group pretest-posttest design which was developed into an experimental and replication class. Samples in this study were 58 students of VIII-A and VIII-B grade in SMPN 46 Surabaya. The data were collected using observation, questionnaires, and tests. The findings revealed that: (1) the implementation of structured inquiry learning got very good category (2) the majority of students’ responses were positive towards the learning process (3) the results of N-gain test for class VIII-A increased in the high category and VIII-B increased in the medium category (4) the results of the unpaired t-test showed that the N-gain score VIII-A was the same as the N-gain score VIII-B. Based on these results, it can be concluded that the implementation of the structured inquiry learning model can improve students’ basic SPS.